Synchronizing Sharia Financial Institution Qanun with National Regulations to Support MSMEs in Aceh - Faisal, Faisal; Mukhlis, Mukhlis; PG, Eko Gani; Muksalmina , Muksalmina; Amalia, Nanda (Jurnal Ilmiah Peuradeun, 2025)
Law Number 11 of 2006 on the Government of Aceh provides a strong legal foundation for implementing Qanun Aceh Number 11 of 2018 concerning Sharia Financial Institutions. However, its effective integration with Indonesia’s national regulatory framework remains a persistent challenge. This study examines the synchronization between the Qanun and national legislation in the Sharia financial services sector, particularly in supporting the development of micro, small, and medium enterprises (MSMEs) in Aceh. Employing an empirical legal method combined with a qualitative approach, the research collected primary data from Sharia Financial Institutions in Aceh and secondary data through an extensive review of academic literature and policy documents. The findings indicate that harmonizing local and national regulations is essential for strengthening the Sharia banking system, ensuring legal certainty, and enhancing financial inclusion for MSMEs. The study proposes a synchronization model emphasizing collaborative efforts among government authorities, Sharia financial institutions, and MSMEs. Such integration is expected to foster sustainable economic growth while reinforcing Aceh’s unique legal autonomy within Indonesia’s constitutional framework. This study contributes to the discourse on legal pluralism, financial governance, and regional economic empowerment in post-conflict and special autonomy regions.